1975
DOI: 10.1002/pssa.2210310115
|View full text |Cite
|
Sign up to set email alerts
|

HVEM in-situ observations of dislocation behaviour in strongly electron-irradiated nickel

Abstract: Nickel foils which were damaged by the irradiation of high‐energy electrons at room temperature in a high voltage electron microscope (HVEM) were deformed in‐situ while under observation and the behaviour of dislocations was studied. The behaviour of dislocations in the damaged crystal is different from that in the undamaged one. In the damaged crystals dislocation channeling is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In nanowires or pillars irradiated intentionally (nuclear nanostructures) or accidentally (FIB manufacturing) and subjected to mechanical loading, the plastic deformation is controlled by the nucleation of dislocations (dislocation source dependent) as well as the interaction of glissile dislocations with point defect clusters generated by irradiation. These interactions were studied experimentally using in situ straining TEM (Saka et al, 1975; Suzuki et al, 1991; Robachy et al, 2003) and predicted using molecular dynamic (MD) and dislocation dynamics simulations (de la Rubia et al, 2000; Osetsky et al, 2000; Zbib et al, 2000) in bulk irradiated materials. Most of these studies showed that SFT can annihilate under applied stress when meeting gliding dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…In nanowires or pillars irradiated intentionally (nuclear nanostructures) or accidentally (FIB manufacturing) and subjected to mechanical loading, the plastic deformation is controlled by the nucleation of dislocations (dislocation source dependent) as well as the interaction of glissile dislocations with point defect clusters generated by irradiation. These interactions were studied experimentally using in situ straining TEM (Saka et al, 1975; Suzuki et al, 1991; Robachy et al, 2003) and predicted using molecular dynamic (MD) and dislocation dynamics simulations (de la Rubia et al, 2000; Osetsky et al, 2000; Zbib et al, 2000) in bulk irradiated materials. Most of these studies showed that SFT can annihilate under applied stress when meeting gliding dislocations.…”
Section: Resultsmentioning
confidence: 99%